'A live film'? Failing to notice television. Issue 1 (1st April 2013) - Mills, Brett
Why does so much television go unnoticed? This article examines the coverage of the Opening Ceremony of the London 2012 Olympic Games to show how some media forms – especially film and music – are a part of everyday debates about culture, whereas television is not. The Opening Ceremony was often about television, and was consumed by billions via television – yet reviews and commentaries about the event rarely mention television at all. This article shows that those involved in the Ceremony who have worked successfully in television – such as Danny Boyle and Rowan Atkinson – are similarly commonly understood via their work in other media. The article calls for those in Television Studies to be more vocal about the work the field does, in order to combat such erasing of television found in Danny Boyle's description of the Opening Ceremony not as television, but as 'live film'.